Molecular Detection and Genetic Analysis of Lumpy Skin Disease Virus (LSDV) in India - Srinivas, Mouttou Vivek; Sambath, Uma; Darmalingam, Selvi; Vasu, Jayalakshmi; Mukhopadhyay, Hirak Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Lumpy skin disease (LSD) is a contagious trans-boundary viral disease of cattle, caused by lumpy skin disease virus (LSDV) under the genus Capripoxvirus of Poxviridae family. The genus Capripoxvirus also comprises goatpox virus (GTPV) and sheeppox virus (SPPV), which affect sheep and goat respectively and are antigenically similar to LSDV. LSD has recently been spread in Asia following outbreaks in the Middle East and Europe. The present study is aimed with the objective of molecular characterization and genetic analysis of LSD virus obtained from the infected cattle in Puducherry, India. PCR confirms the presence of the LSDV genome in the clinical sample. Phylogenetic analysis and complete assessment of multiple sequence alignments between LSDV, GTPV and SPPV P32 gene sequences revealed least variation between sheeppox virus and LSD virus (1.5% variation) and highest variation between sheeppox and goatpox virus (2.8% variation). Based on the present study, it is also confirmed and concluded that P32 gene can be used for differentiating LSD, sheeppox and goatpox viruses. The phylogenetic analysis revealed that the LSDV under this study was clustered in a separate clade with the other LSDV sequences of Turkey, Kazakhstan, Kenya, Russia, Serbia, Nigeria and other Indian LSDV sequences available in the GenBank. The query LSDV sequence was closely related with other LSD viruses circulating in India suggesting a single LSDV strain is circulating in the country. This result underlines the importance of continuous monitoring and characterization of circulating strains.